Transition to Christianity. Art of Late Antiquity, 3rd- 7th Cenury AD, p.p. 122-123 (n. 80-81), 150-151 (n. 118) - Μακροπούλου, Despina Makropoulou / Δέσποινα (Catalogue of the Exhibition held at the Onassis Cultural Center (ed. Anastasia Lazaridou), New York City, December 7, 2011 – May 14, 2012)
Transition to Christianity. Art of Late Antiquity, 3rd- 7th Cenury AD, p.p. 122-123 (n. 80-81), 150-151 (n. 118)